Innovative Pharmacotherapy Strategies for Benign Meningiomas: A Case Study and Review of Evidence-Based Practices - Aamir Jalal Al-Mosawi (International Journal of Pharmaceutical & Biological Archive, 2024)
Meningiomas are predominantly benign, slowly growing tumors that primarily affect females and can lead to significant morbidity due to pressure effects on adjacent structures and increased intracranial pressure. This article reviews the historical context of meningioma treatment, highlights a case study of a 35-year-old female with meningioma, and explores pharmacotherapeutic options, particularly the use of hydroxyurea in combination with tamoxifen. While traditional surgical and radiotherapeutic approaches have limitations, evidence suggests that hydroxyurea may effectively induce tumor regression and manage symptoms, particularly in patients with unresectable or recurrent tumors. The proposed combination therapy aims to enhance treatment efficacy while minimizing adverse effects. This multifaceted approach underscores the importance of personalized medicine in the management of benign meningiomas, advocating for further research to optimize outcomes.